Development and Application of Videoconferencing Systems - Macura, Arijana; Peraković, Dragan (Promet - Traffic&Transportation, 2005)
Videoconferencing is the best-known form of teleconferencing.It allows concwrent transmission of images and soundvia computer network for the communication of several personsphysically distant in real time. The computers are networkedand additionally equipped with camera, microphone,voice and video card, and adequate programmes. Video signalsare digitized and compressed before network transmission. Studentsand lecturers may lead discussions and exchange documentsand other malelials via the computer.